Human CD6 Down-Modulation following T-Cell Activation Compromises Lymphocyte Survival and Proliferative Responses - Carrasco, Esther; Escoda-Ferran, Cristina; Climent, Núria; Miró-Julià, Cristina; Simões, Inês T.; Martínez-Florensa, Mario; Sarukhan, Adelaida; Carreras, Esther; Lozano, Francisco (Frontiers in Immunology, 2017)
Available evidence indicates that the CD6 lymphocyte surface receptor is involved in T-cell developmental and activation processes, by facilitating cell-to-cell adhesive contacts with antigen-presenting cells and likely modulating T-cell receptor (TCR) signaling. Here, we show that in vitro activation of human T cells under different TCR-ligation conditions leads to surface downregulation of CD6 expression. This phenomenon was (i) concomitant to increased levels of soluble CD6 (sCD6) in culture supernatants, (ii) partially reverted by protease inhibitors, (iii) not associated to CD6 mRNA down-regulation, and (iv) reversible by stimulus removal. CD6 down-modulation inversely correlated with the upregulation of CD25 in both FoxP3− (Tact) and FoxP3+ (Treg) T-cell subsets. Furthermore, ex vivo analysis of peripheral CD4+ and CD8+ T cells with activated (CD25+) or effector memory (effector memory T cell, CD45RA−CCR7−) phenotype present lower CD6 levels than their naïve or central memory (central memory T cell, CD45RA−CCR7+) counterparts. CD6lo/− T cells resulting from in vitro T-cell activation show higher apoptosis and lower proliferation levels than CD6hi T cells, supporting the relevance of CD6 in the induction of proper T-cell proliferative responses and resistance to apoptosis. Accordingly, CD6 transfectants also showed higher viability when exposed to TCR-independent apoptosis-inducing conditions in comparison with untransfected cells. Taken together, these results provide insight into the origin of sCD6 and the previously reported circulating CD6-negative T-cell subset in humans, as well as into the functional consequences of CD6 down-modulation on ongoing T-cell responses, which includes sensitization to apoptotic events and attenuation of T-cell proliferative responses.